2015
DOI: 10.1186/s12889-015-2586-4
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of the perceived risks of electronic cigarette and hookah use in pregnancy

Abstract: BackgroundStudies reveal that electronic cigarette (e-cigarette) and hookah use are increasing among adolescents and young adults. However, the long-term health effects are unknown, especially with regards to pregnancy. Because of the increased use in women of reproductive age, and the unknown long-term health risks, our primary objectives were to determine the perceived risks of e-cigarette and hookah use in pregnancy, and learn common colloquial terms associated with e-cigarettes. Furthermore, we sought to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 43 publications
1
59
1
4
Order By: Relevance
“…192194,214,288,325327,332,335,336,338,353,354,361,369,372,374,382,384,389,390,446,448,449,453457,461464,467,471474,476,477,484,485,488,490,492,493,495,502,503 In the U.S. and Great Britain, this belief has eroded over time with more individuals mistakenly believing ENDS are as harmful or more harmful that cigarettes. 391,414 Studies suggest that ENDS are also perceived as less addictive than cigarettes, 367,375,403,446 tools that may help users reduce or quit smoking, 320,327,330,338,357,374,448,453,455,458,461,464,467,481,483,485,486,488,493,495,499 less expensive than cigarettes, 335,338,447,455,456,472,499 and more convenient or easier to use than cigarettes. 335,338,357,400,499 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…192194,214,288,325327,332,335,336,338,353,354,361,369,372,374,382,384,389,390,446,448,449,453457,461464,467,471474,476,477,484,485,488,490,492,493,495,502,503 In the U.S. and Great Britain, this belief has eroded over time with more individuals mistakenly believing ENDS are as harmful or more harmful that cigarettes. 391,414 Studies suggest that ENDS are also perceived as less addictive than cigarettes, 367,375,403,446 tools that may help users reduce or quit smoking, 320,327,330,338,357,374,448,453,455,458,461,464,467,481,483,485,486,488,493,495,499 less expensive than cigarettes, 335,338,447,455,456,472,499 and more convenient or easier to use than cigarettes. 335,338,357,400,499 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…These have all been a cause for serious concern; however, two recent developments in the field have greatly added to the importance of the consequences of smoke/nicotine exposure on the developing fetus: It has been unequivocally demonstrated that the effects of maternal smoke/nicotine exposure on the developing fetus are not limited to the exposed progeny, but are also transmitted to subsequent generations' offspring, even though those generations never encountered smoke or nicotine (Rehan et al, ; Rehan, Liu, Sakurai, & Torday, ). These findings provide a renewed Lamarckian perspective to the effects of smoke/nicotine exposure on the developing fetus (Pilpel & Rechavi, ; Skinner, ). Because e‐cigs are perceived by many as a safer alternative during pregnancy, their use has increased sharply among women of reproductive age (Baeza‐Loya et al, ; Kahr et al, ; Li, Saad, Oliver, & Chen, ; Nguyen, Tong, Marynak, & King, ; Oncken et al, ; Wapner et al, ). Sales data project that the use of e‐cigs will soon surpass compared to conventional cigs; hence, the problem will likely become worse ( https://www.cnbc.com/id/100991511).…”
Section: Introductionmentioning
confidence: 99%
“…Such measures are aimed at their removal from shelves and websites that are accessible to minors. In addition, an increasing number of pregnant women, and women of reproductive age, are turning to electronic cigarettes as an alternative to tobacco-based cigarettes in an effort to diminish the adverse developmental effects of exposure to cigarette smoking (Baeza-Loya et al, 2014;Kahr, Padgett, Shope, et al, 2015;Kurti et al, 2017;McCubbin, Fallin-Bennett, Barnett, & Ashford, 2017;Oncken, Ricci, Kuo, et al, 2017;Suter, Mastrobattista, Sachs, & Aagaard, 2015;Wagner et al, 2017).…”
mentioning
confidence: 99%